Crystal structure and stability of phases in Mg-Zn alloys: A comprehensive first-principles study. (1st January 2023) - Cheng, Du; Wang, Kang; Zhou, Bi-Cheng
Abstract: Mg-Zn alloys form the basis of a wide variety of commercial light-weight Mg alloys due to their precipitation hardenability, biocompatibility, and low cost. Despite significant progress, there exist controversies over the crystal structures and stabilities of various complex precipitates in this important binary system. In this work, the information about crystal structures and stabilities of phases in Mg-Zn system is critically reviewed and three key open questions are identified: (1) What are crystal structures of Guinier-Preston (GP) zones? (2) What are relative stabilities of a myriad of phases observed for β 1 ′ precipitates? (3) Why does the β 2 ′ phase have two distinct orientation relationships (ORs) with α -Mg? To shed light on these questions, comprehensive first-principles calculations based on density functional theory, cluster expansion, and Monte Carlo simulations are performed. The atomic structures of GP zones are predicted, and the effect of coherency strain on their stabilities are analyzed. The structures of β 1 ′ precipitates composed of the rhombic MgZn2 and the elongated hexagonal Mg6 Zn7 units are provided. It is shown that the β 1 ′ precipitate can be stabilized with increased fraction of rhombic MgZn2 units, which leads to local regions of the C14 MgZn2 Laves phase. The origin of the two distinct ORs between β 2 ′ phase and the matrix is traced back to two formation paths, i.e., relaxation of the coherent Zn ordering on HCP matrix and coarsening of C14 MgZn2 region in β 1 ′ precipitates. Finally, a feasible precipitation sequence in Mg-Zn alloys is suggested. Graphical abstract: Image, graphical abstract